Characterization of surface decorations in Prehispanic archaeological ceramics by Raman spectroscopy, FTIR, XRD and XRF - Centeno, Silvia A. (2012)
Non-invasive Raman microspectroscopy, FTIR, μXRD and XRF were used to identify the materials present in the black, red, and white surface decorations in selected pottery wares from two Prehispanic archaeological sites in Northwestern (NW) Argentina (AD 900?1530). The iron manganese spinel jacobsite, MnFe2O4, was found to be the main component of two of the fired black decorations analyzed, while hematite and amorphous silicates were found to be present in the red and white fired decorations, respectively. This is the first study, to our knowledge, that firmly identifies jacobsite in black decorations in Prehispanic archaeological ceramics. In fragments recovered from one site, a carbon-based black pigment was identified while gypsum was observed in the recessed areas of decorative surface incisions. Gypsum, potassium nitrate and halite, most likely deposited during burial, were observed on the surface of some of the fragments analyzed. The results are discussed in the context of the technological processes involved and are compared to compositions previously reported for decorations in ceramic objects from NW Argentina.